iCa2+ Flux, ROS and IL-10 Determines Cytotoxic, and Suppressor T Cell Functions in Chronic Human Viral Infections - Mohanty, Subhasmita; Barik, Prakash; Debata, Nagen; Nagarajan, Perumal; Devadas, Satish (Frontiers in Immunology, 2020)
Exhaustion of CD8+ T cells and increased IL-10 production is well known in chronic viral infections but mechanisms leading to loss of their cytotoxic capabilities and consequent exhaustion remain unclear. Exhausted CD8+T cells also called T suppressors are highly immuno suppressive with altered T cell receptor signaling characteristics that mark it exclusively from their cytotoxic counterparts. Our study found that iCa2+ flux is reduced following T cell receptor activation in chronically activated murine CD8+ T cells or CD8+ T cells from chronic Hepatitis B patients when compared to their effector counterparts. Importantly chronic activation of murine cytotoxic CD8+ T cells lead to reduced iCa2+ in flux, decreased IFN-andenhanced IL-10 production and this profile is mimicked in Tc1 cells upon reduction of iCa2+ flux by extracellular calcium channel inhibitors. Further reduced iCa2+ flux induced ROS which lead to IFN-reduction and increased IL-10 producing T suppressors through the STAT3 - STAT5 axis. The above findings were substantiated by our human data where reduced iCa2+ flux in chronic Hepatitis infections displayed CD8+ T cells with low IFN- and increased IL-10 production. Importantly treatment with an antioxidant led to increased IFN- and reduced IL-10 production in human chronic Hep-B samples suggesting overall a proximal regulatory role for iCa2+ influx, ROS and IL-10 in determining the effector/ suppressive axis of CD8+ T cells.